The big sleep - Chandler, Raymond 1888-1959 (Warner Home Video, 2000)
L.A. private eye Philip Marlowe takes on a blackmail case and follows a trail peopled with murderers, pornographers, nightclub rogues and the spoiled rich.
Orig.: USA 1946. Sprachen: Engl., Franz., Ital. - Untertitel auch dt.
Keywords: The big sleep; Mystery films; Marlowe, Philip (Fictitious character) -- Drama; Private investigators -- California -- Los Angeles -- Drama; Los Angeles (Calif.) -- Drama; Detective and mystery films; Feature films; Film adaptations; Film noir; Gangster films; Video recordings for the hearing impaired